Interaction of thymidine with sodium bis(2-ethylhexyl) sulfosuccinate in alcohol and water: Studies with UV-Vis technique - Paudel, Indu M; Bhattarai, Ajaya (Pharmaceutical Sciences and Research, 2020)
The accurate measurement of thymidine absorbance in the presence of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) in ethanol and water systems at room temperature by UV-vis technique has been reported. The AOT concentrations varied from 0.0005 to 0.014 [mol/L] in ethanol whereas from 0.0002 to 0.042 [mol/L] in water. The concentration of thymidine was 0.0073 [mol/L] during UV-vis spectrum registration. The thymidine spectrum was examined in the presence of AOT concentration. Using a statistical method of non-linear regression (NLREG), thymidine binding and thymidine distribution constants were evaluated. A noticeable decrease in thymidine absorbance in the presence of AOT concentration was shown in the water system; whereas, in the ethanol system, just the opposite trend has been found. The results are discussed in the context of binding and distribution constants in the studied systems.